2014
DOI: 10.3233/isu-140742
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards open access: A meta-synthesis of the empirical literature

Abstract: Abstract. The aim of the present study is to report the results of a meta-synthesis of the empirical literature on scholars' attitudes towards Open Access (OA) journals. A total of 16 articles published in scholarly journals since 2002 (when the Budapest Open Access Initiative was released) were included in the study and five major themes emerged from their examination and analysis. The literature indicates that attitudes and perceptions of OA are varied across countries and across disciplines. Free access, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 21 publications
4
37
0
1
Order By: Relevance
“…Publications such as rapid communications, short communication, technical notes, letters to the editor, books, article reviews, viewpoints, editorials, and calendar events, were excluded. Our criteria is similar to those used by Grandbois and Beheshti [42], Liu and Wan [21], and Togia and Korobili [43].…”
Section: Methodsmentioning
confidence: 99%
“…Publications such as rapid communications, short communication, technical notes, letters to the editor, books, article reviews, viewpoints, editorials, and calendar events, were excluded. Our criteria is similar to those used by Grandbois and Beheshti [42], Liu and Wan [21], and Togia and Korobili [43].…”
Section: Methodsmentioning
confidence: 99%
“…Togia and Korobili's (2014) (Frass, Cross & Gardner, 2014. p. 7). In May 2012, Wiley conducted a survey of its authors; of the 10,000 authors who responded, one third indicated having published in an OA journal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concern and confusion about APCs also permeate researchers' responses in a variety of studies (Fowler, 2011;Moore, 2011;Togia & Korobili, 2014). As noted in the introduction, many players in the scholarly publishing world conflate OA journals with APCs, leading researchers to assume that all OA journals charge APCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal, personal, or individual values and differences are suggested to influence scholarly publishing (Dulle & Minishi-Majanja, 2011;Khalili & Singh, 2012;Togia & Korobili, 2014). Internal, personal, or individual values and differences are suggested to influence scholarly publishing (Dulle & Minishi-Majanja, 2011;Khalili & Singh, 2012;Togia & Korobili, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, external influences such as perceptions of journal quality are not the only motivational factors driving academic achievement. Internal, personal, or individual values and differences are suggested to influence scholarly publishing (Dulle & Minishi-Majanja, 2011;Khalili & Singh, 2012;Togia & Korobili, 2014). Spanning decades, social psychology has both empirically and theoretically investigated individuals' concepts of self-identity and selfcategorization (Stets & Burke, 2000;Tajfel, Billig, Bundy, & Flament, 1971;Turner, 1985), and how these structures are shaped and interact in various social and organizational settings (Ashforth & Mael, 1989;Hogg & Terry, 2000).…”
Section: Introductionmentioning
confidence: 99%